Avaliação de desempenho superficial de tintas arquitetônicas de mercado: estudo de caso - Fabio das Neves Donadio (2011)
When analyzing the history of a communitys culture, we notice that it is marked by constancy and environment and socioeconomic changes that relate directly to the emergence of new individual and collective habits. These new habits, frequently marked in the intangible and tangible elements of our culture, manifest in the architecture in a quiet and constant form and they are responsible, many times, for its final aspect. Inserted in a dynamic process, new materials, financial resources, techniques and preferences modify and construct, in a slowly way, the buildings that compose the urban landscape. The insertion of these new materials in the conservation of buildings is not forbidden. However, its indication must be made on formal criteria and experimentations capable to prove its effectiveness, avoiding damages to the cultural goods and the urban landscape. To discuss in a philosophical way its indication, the present article aims to identify how some of the main theories of restoration and patrimonial letters evaluate or comment the use of new materials in the conservation/restoration processes of immovable cultural goods and how its concepts carry the hypothetical use of market modern inks when used on a historical raw land prototype a construction technique originally coated with whitewash or other porous mineral materials. It still aims to present general aspects about the appropriate coverings of these buildings, testing and characterizing the modern options of inks, currently available in the Brazilian market.